DI BALIK ANGKA POU: MENGUNGKAP PERAN FAKTOR SOSIAL EKONOMI DALAM KETAHANAN PANGAN - Dian Nahryah; Erwin Tanur (Badan Perencanaan Pembangunan, Riset dan Inovasi Daerah Kabupaten Sragen, 2026)
The Prevalence of Undernourishment (PoU) is an important indicator for assessing a region’s food security. PoU reflects not only food availability but also the population’s ability to access and consume nutritious food. Data from 2024 show considerable variation in PoU levels across districts and cities in Indonesia, indicating differences in socioeconomic conditions among regions. These disparities highlight the need to examine the socioeconomic factors influencing PoU at the regional level. This study aims to analyze the influence of socioeconomic factors on PoU levels in 514 districts and cities in Indonesia in 2024. The data were obtained from publications of Statistics Indonesia (BPS) and analyzed using binary logistic regression to identify variables that significantly affect the likelihood of undernourishment. The results show that poverty rate, Human Development Index (HDI), and access to improved drinking water have significant effects on PoU. Regions with better welfare and basic services tend to have lower PoU levels. These findings emphasize the importance of policies focusing on poverty reduction, human development improvement, and equitable access to basic services to strengthen regional food security sustainably. Keywords: Poverty, Human Development Index (HDI).